Velocardiofacial syndrome with a rare t(2;22) - Huber, Jair; Rainho, Claudia A.; Gomes, Marcus V.; Santos, Silvio A.; Ramos, Ester S. (Wolters Kluwer, 2007)
Rearrangements involving chromosomes 2 and 22 were described not only as acquired abnormalities in a variety of human neoplasias but also in the constitutional karyotype suggesting the existence of a greater fragility in some specific regions in these chromosomes. Patients with DiGeorge and Velocardiofacial syndromes have a deletion on 22q11 leading to haploinsufficiency for one or more gene(s). We report a patient with velocardiofacial syndrome in which cytogenetic and fluorescence in situ hybridization analysis showed a rare t(2;22) and deletion in the 22q11 region. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: Chromosome 2; Chromosome 22q11; t(2, 22); Velocardiofacial syndrome; behavior disorder; case report; child; chromosome 2; chromosome 22; chromosome deletion; cytogenetics; DiGeorge syndrome; echocardiography; electroencephalogram; face malformation; fluorescence in situ hybridization; focal epilepsy; heart murmur; human; karyotype; learning disorder; male; priority journal; velocardiofacial syndrome; Child, Preschool; Chromosomes, Human, Pair 2; Chromosomes, Human, Pair 22; DiGeorge Syndrome; Humans; Karyotyping; Male; Translocation, Genetic